Sectoral Linkages in Assam: an Empirical Analysis. - Das, Ira, Dutta, Mrinal Kanti and Borbora, Saundarya (2010)
Assam, a state of North East India, is an agriculture-based underdeveloped state. Literature indicates that the agriculture sector’s linkages with non-agricultural activities are not strong in the state. Therefore, an attempt is made in this paper to examine the present nature and strength of the sectoral linkages in the state with the help of the input-output analysis on the basis of the available recent data. Weak sectoral linkage is established from the study as only 5 per cent of the sectors have a high value of backward and forward linkages. Earlier studies indicated that as leakages increased owing to increase in imports, reduction in the multiplier effect was observed. Therefore, it is imperative to estimate backward and forward linkages with and without import leakages. An attempt is made here to compare the linkage effects with and without import leakages to capture the “potential linkages” in the state. The study reveals that some sectors like paddy, fibre crops, plantations, etc. have the potential of high backward and forward linkages if import leakages are allowed. Inter-sectoral linkages should be improved for the economic development of the state.